Evaluation and comparison of antibiotic susceptibility profiles of Streptomyces spp. from clinical specimens revealed common and region-dependent resistance patterns - Kotrbová, Lucie; Lara, Ana Catalina; Corretto, Erika; Scharfen, Josef; Ulmann, Vít; Petříčková, Kateřina; Chroňáková, Alica (Scientific reports, 2022)
Notwithstanding the fact that streptomycetes are overlooked in clinical laboratories, studies describing their occurrence in disease and potential pathogenicity are emerging. Information on their species diversity in clinical specimens, aetiology and appropriate therapeutic treatment is scarce. We identified and evaluated the antibiotic susceptibility profile of 84 Streptomyces clinical isolates from the Czech Republic. In the absence of appropriate disk diffusion (DD) breakpoints for antibiotic susceptibility testing (AST) of Streptomyces spp., we determined DD breakpoints by correlation with the broth microdilution method and by the distribution of zone diameters among isolates. Correlation accuracy was high for 9 antibiotics, leading to the establishment of the most valid DD breakpoints for Streptomyces antibiotic susceptibility evaluation so far. Clinical strains belonged to 17 different phylotypes dominated by a cluster of strains sharing the same percentage of 16S rRNA gene sequence identity with more than one species (S. albidoflavus group, S. hydrogenans, S. resistomycificus, S. griseochromogenes; 70% of isolates). AST results showed that Streptomyces exhibited intrinsic resistance to penicillin, general susceptibility to amikacin, gentamycin, vancomycin and linezolid, and high percentage of susceptibility to tetracyclines and clarithromycin. For the remaining antibiotics, AST showed inter- and intra-species variations when compared to available literature (erythromycin, trimethoprim-sulfamethoxazole), indicating a region-dependent rather than species-specific patterns.
Keywords: antibakteriální látky; RNA ribozomální 16S; Microbial Sensitivity Tests; linezolid; Streptomyces; Linezolid; Anti-Bacterial Agents; mikrobiální testy citlivosti; RNA, Ribosomal, 16S